Optimization of a mechanical test on composite plates with the virtual fields method - Syed Muhammad, Kashif; Toussaint, Evelyne; Grédiac, Michel (Springer Publishing Company, 2009)
This paper deals with the optimization of a mechanical test performed on a composite plate specimen. Heterogeneous stress fields which take place in the plate specimen are processed with the virtual fields method to identify the bending rigidities. Various design parameters such as the support locations or the specimen shape are optimized in the present work. Results obtained are discussed and the best compromise between the quality of the results and the convenience in the practical realization of the tests is proposed.